Vertical Integration and Valuation of International Oil Companies - Bård Misund; Petter Osmundsen; Marius Sikveland (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper studies financial statement information from the 50 largest international oil and gas companies during 1992 to 2011 and evaluates their relation to market values. In particular, we examine how this relationship is affected by accounting method choice (successful efforts versus full cost accounting) and vertical integration. We find that net income is more value relevant for full cost companies compared to companies that use the successful efforts accounting method. Furthermore, the value relevance of oil and gas reserves is different among successful efforts and full cost companies. Larger reserves among successful efforts companies are awarded a premium by stock markets. The value relevance of book value is significantly lower for integrated companies than for pure upstream companies. We also find that the value relevance of oil and gas reserves is different for upstream and integrated companies.
Keywords: F23; G00; L71; M41; 330; company valuation; value-relevance; financial analysis; oil and gas industry